Peranan Hakim Dalam Upaya Penegakkan Hukum Di Indonesia (Lex Jurnalica, 2012)
AbstractLaw enforcement needs strong structuring. As said by Satjipto Rahardjo, that law enforcement (modern) is run by the components of the civil servant officer. Therefore, the behavior of the legal structure of the civil servant officer in Indonesia becomes very important to be highlighted in the process of law enforcement. Law enforcement in Indonesia is still not fit from what is expected, one reason is still a difference between theory and practice. Between the rules and the practice is still very much there are differences that cause we always find it difficult to build a state of law. In this study will be the discussion is about,